Intelligent mobile walking-aids: perception, control and safety. (2nd January 2020) - Yan, Qingyang; Huang, Jian; Tao, Chunjing; Chen, Xinxing; Xu, Wenxia
Abstract : Robot-assisted walking has become a popular research field for helping mobility-limited people to walk more easily. Different from other walking-aid devices (e.g. exoskeletons and prosthesis), intelligent mobile walking-aids (IMWs) are invented for helping the visually impaired or people in need (e.g. the elderly) to walk in daily life. This paper reviews various related literatures on IMWs and dwells on three kinds of perception systems and perception algorithms of IMWs to explain how IMWs understand the user's motion states or tendency. Besides, the control strategies of IMWs under the normal case concerned are classified and compared. The safety measures for preventing the user from abnormal cases (e.g. encountering obstacles, the user's stumbling and falling, faults of IMWs) are introduced in detail as well. The performance of current safety measures for the user's fall detection and prevention has been evaluated and concluded. At the end of the article, the discussion and perspective of IMWs are presented. GRAPHICAL ABSTRACT: